Stem cells: the evidence for their application in trauma and orthopaedics. Issue 4 (August 2022) - Vergara Jalandoni, Diego Leopoldo; Grewal, Urpinder; Stott, Philip
Abstract: The application of stem cells, or mesenchymal stem cells (MSC), in trauma and orthopaedics has been growing quickly in the last few decades. MSCs can be applied in tissue regeneration because of their function as a 'site-regulated drugstore' as described by Caplan in their release of trophic and immunomodulatory agents to aid focal tissue regeneration. This has been applied to multiple orthopaedic conditions such as osteoarthritis, focal non-unions, osteonecrosis in the femoral head, and ligamentous injuries. The purpose of this review is to summarize the current use of stem cell therapy in orthopaedics alongside the respective evidence. There is preliminary evidence that explores the use of MSCs in orthopaedic conditions which show promise and if developed successfully can positively impact patients whilst saving costs of surgery and minimizing risk. However the presence of low-quality clinical studies and a multitude of unregulated musculoskeletal stem cell therapy clinics that are not supported by the current evidence which is misleading public opinion and expectations. The development of MSCs has its challenges, such regulatory obstacles which can delay a development of a standardized method in preparing MSCs. Further studies with large patient populations and randomized control trials are required to support the use of stem cell treatment over currently available treatments.